Current and emergent pharmacologic treatments for irritable bowel syndrome with diarrhea: evidence-based treatment in practice. (February 2017) - Lucak, Susan; Chang, Lin; Halpert, Albena; Harris, Lucinda A.
Irritable bowel syndrome with diarrhea (IBS-D) is a common, chronic functional gastrointestinal disorder with symptoms that can be distressing for patients and often result in substantially impaired quality of life. This review focuses on providing clinicians with information on practical, evidence-based treatment for IBS-D. Current therapies commonly used for the treatment of IBS-D, including pharmacologic and nonpharmacologic interventions, are briefly reviewed, followed by discussion of the emergent pharmacologic treatments (rifaximin and eluxadoline) and medical foods (IBgard ® and EnteraGam ® ). Given the lack of a standard treatment algorithm for IBS-D and the emergence of new pharmacologic therapies, treatment needs to be tailored to the individual patient and take into account the severity of disease. In this context, the latter part of this manuscript examines how treatments for IBS-D can be used in clinical practice by presenting three patient case scenarios with varying degrees of IBS-D severity. For each case, the patient's medical history and clinical presentation are related to the Rome Foundation multidimensional clinical profile (MDCP) and potential treatment options with current and emergent therapies are reviewed. The interplay of gastrointestinal symptoms and their psychosocial impact, as well as the importance of a patient-centered approach to therapy, are discussed. Consideration is given to the potential need for combination therapies and how emergent treatments could fit into the treatment pathway for mild, moderate, and severe cases of IBS-D in clinical practice.